ENGLISH LANGUAGE DEVELOPMENT OF YOUNG LEARNER WITH VISUAL LEARNING STYLE: A CASE STUDY - ADI NUGRAHA, SETIA (Language Horizon: Journal of Language Studies, 2014)
ENGLISH LANGUAGE DEVELOPMENT OF YOUNG LEARNER WITH VISUAL LEARNING STYLE: A CASE STUDY Setia Adi Nugraha English Literature, Faculty of Languages and Arts, State University of Surabaya nugraha.setia.adi@gmail.com Widyastuti, SS, M. Pd English Language and Literature Department, Faculty of Languages and Arts, State University of Surabaya wid_unesa@yahoo.com ABSTRAK Studi ini focus dalam perkembangan bahasa anak dengan gaya belajar visual dan menemukan hubungan antara kepribadian dengan gaya belajar. Perkembangan bahasa dapat dilihat dari bagaimana anak/siswa mempraktikan diri dan pembelajaran terjadi via hubungan stimuli-respon (Ellis 1985; Ellis 1997). Pembelajaran bahasa kedua terikat dengan gaya belajar karena gaya belajar dianggap sebagai kunci dari aktivitas belajar bahasa (Dornyei 2005)dan meliputi sifat alami individu, kebiasaan dan cara-cara tertentu dalam menyerap, memproses serta menyimpan informasi dan skill (Reid 1995a; Dornyei 2005) beserta aspek psikologis untuk merespon lingkungan belajar (Keefe 1979a). Lalu, kepribadian berdiri sebagai kunci penting pada pembelajaran bahasa kedua karena ini mempengaruhi kemampuan sosial pada anak (Ellis 1985), anak/siswa pada penelitian ini adalah siswa berumur 4 tahun. Terdapat 4 (empat) tipe kepribadian, koleris, plegmatis, sanguin dan melankolis (Littauer 1992; Suyadi 2010). Penelitian ini adalah deskriptif-kualitatif dan menggunakan siswa berumur 4 tahun, siswa di kelas K1, Ivy School sebagai subyek penelitian. Data diambil dari interaksi antara siswa dengan para guru. Lalu, untuk mengetahui kepribadiannya, maka penelitian ini dilengkapi dengan memberikan uji kepribadian. Berdasarkan hasil analisis data, beberapa fakta terungkap seperti anak dengan gaya belajar visual memiliki berbagai gaya spesifik dalam proses pemerolehan bahasa, yakni melalui mengimitasi, meniru setelah mendapatkan stimuli dan ‘penguatan’ dari para guru. Terlebih, penelitian ini juga menemukan bahwa dia memiliki dua tipe kepribadian yang berbeda, sanguine sebagai mayor dan melankosis sebagai minor yang serta merta mempengaruhi gaya belajarnya. Kata Kunci: Perkembangan Bahasa, Pembelajaran Behavioris, Gaya Belajar, Kepribadian ABSTRACT This study focuses in the language development of young learner with visual learning style and also find the relationship between personality with learning style. The language development can be viewed from how the learner practices in learning activity. According to Ellis, behaviorist concentrates in habit, practice and the learning happens through stimuli-response connection (Ellis 1985; Ellis 1997). Furthermore, Second Language learning has bond through learning style because learning style is treated as the key of language learning activity (Dornyei 2005) and it covers individual’s natural, habitual and preferred way(s) in absorbing, processing also saving new information and skills (Reid 1995a; Dornyei 2005) also psychological features in order to respond the learning environment (Keefe 1979a). Furthermore, personality stands as important key towards Second Language learning because it affects social skills of young learner/children (Ellis 1985), then young learner for this study is a 4-year old student. There are four personality types such as choleric, phlegmatic, sanguine and melancholic (Littauer 1992; Suyadi 2010). This study is descriptive-qualitative research and using the 4-year old student, young learner at K1 Class at Ivy School as the subject. The data are taken from the interactions between him towards the teachers. Then, in order to know about his personality, it is completed by giving personality test to the subject. Based on the data analysis, some facts are revealed such as the young learner with visual learning style has specific ways to acquire language, through imitating, copying after getting stimuli and reinforce from the teachers. Moreover, it also finds that he has two different personality types, sanguine as the major and melancholic as the minor that influence his learning-style. Keywords: Language Development, Behaviorist Learning, Learning Style, Personality INTRODUCTION Learning style is one of part SLA, famous in around 1970s, learning style was becoming the trending topic research in that era, but it was decreased because of too much plethora or labels and also it was lacked of valid and reliable instruments (Dornyei 2005), then the risk of using it as a matter got higher than previous period (Skehan 1998). But, Dornyei keeps his faith in it and he states that learning style is the key in learning Second Language Acquisition (Dornyei 2005). Learning style itself cannot be separated from people’s life and it is generally appeared in preschool period. Then, learning style is being used by the teachers and also children psychiatrist in order to understand about children’s characteristics and know how to treat them. Understanding children’s learning style can help parents and teachers in developing, supporting and also stimulating children in learning activities (Suyadi 2010) and there are four learning styles, such as: visual, auditory, kinesthetic and tactile. Acquiring language needs steps and must passes various levels on it. Human also must be passingsevarl periods in language development and also intelligence development. There are several periods of human’s intelligence: The period of sensori-motor intelligence (birth-2 years old), the period of pre-operational thought (2-7 years old), concrete period (7-11 years old) and formal operational (adolescence-adulthood) (Cecco 1967). During pre-operational thought child is defined as young learner (Linse 2005) and along this period child is fragile and needs psychological and physical attention (Linse 2005). Furthermore, during this period children only focus in one dimension and their perception is ‘centered’ (Cecco 1967). Understanding about children moreover in their learning can be seen from many ways such as personality, Ellis stated that personality frequently affecting social skills of the children and then those skills are used as the control machine in language exposure of Second Language (Ellis 1985). There are four types of personality, choleric, phlegmatic, sanguine and melancholic (Suyadi 2010). Finally, childhood is important period in language development because during that period (2-7 years old) children are entering golden year in learning, learning style and personality also take part in it. This study tries to describe about English language development based on daily learning of young learning with visual learning style at Ivy School Surabaya. There are two research questions for this study, (1) How does young learner with visual learning style acquire language?, (2) What are the relationships between personality and learning style?. This study tries to describe about the process of young learner with visual learning style acquire language and know the relationships between personality and learning style. This study is not only focusing in linguistics but also covering learning activities and psychology area but it is not for learning strategy. This study focuses in kindergarten student, a young learner with visual learning style and the study only takes the data from activities in the classroom, not in another place. Several theories are becoming main cores of this study, such as theory of behaviorist learning theory of Ellis, then Zoltan Dornyei’s theory and also Suyadi in learning style and also Florence Littauer and Suyadi in personality. RESEARCH METHOD This study uses descriptive-qualitative in getting and describing about language development of the young learner with visual learning style and combined with personality. This study needs to be explained by words not by numbers or statistics, because this study is stressing on language development and its relationship with learning style. This study designed for natural setting in the way of picking the data, it means there will be no special treatment during collecting the data. Qualitative research emphasizes in process than in product (Sutopo 1990) and it is definitely matched with this study that concern in the language development. Natural setting research actually same with Piaget’s methodology. When Piaget did his project in language research, he tended to use observation than controlled invention (Cecco 1967), it explains that Piaget let anything went on by its way. The writer does an observation for this study, write actual events depend on reality that happen in that day. The data for this study are utterances, photos. The data itself is taken from from student’s activities and interactions in the class. The source of data for this study is a 4-year old boy, young learner from K1 Class, Ivy School Surabaya, named T. This study only takes one student with visual learning style and also must have personality.The reason of why this study only takes visual, because children usually are visual or auditory, moreover it can be both (DeKeyser 2007). For the personality, it depends on the personality that lies on the visual learner. For this study, the researcher uses observation and equipped by various instruments such as observation sheets and also recorder. There are two techniques for thi study, observation sheets for language developmentwhich is following behaviorist learning theory and test (personality test) in order to know the personality and know the relationships between personality and learning style. In order to answer the research questions, the researcher will collect and read the data based on daily result, then the researcher will process the data according to the theory that used by the researcher. For the research question number one, the researcher will use behaviorist learning theory in Rod Ellis’s book Understanding Second Language Acquisition and Brown’s book Principles of Language Learning and Teaching, and another book source depends on the writer needs. Then, in answering the research question number two, the researcher will use theory of learning styles in Zoltan Dornyei’s book Psychology of Language Learner – Individual Differences in SLA and another supporting books in order to strengthen the theory. RESULTS AND DISCUSSION In results section will be divided into two parts because of this research has two different scopes to talk, the way of young learner with visual learning style acquire language and the result of personality test. This research done in three days between 2 (two) weeks, then only observed one student named, T in K1 Class, Ivy School Surabaya and there were two teachers there, Miss A as the main teacher and Miss B as the teacher assistant. The learning activities started at 07.30am-10.30am, every Wednesday until Friday and this research did on January 10th, 2014, January 15th, 2014 and January 17th, 2014. Based on three days of research, this study finds many utterances come out from the students and also from the teachers. Each conversations below shows specific results in the way of T in learning language. Conversation 1 Miss A (S): “What is the opposite of ‘small’? T & Friends (RS): (No response from the students, and also T. Then, Miss A was repeating her question) Miss A (RF): “What is the opposite of ‘small’ guys? (While she asked the students, she also acted something big) T & Friends (P): “Biiiiig!” (All together) Conversation 1 explains about when T got stimuli but he did not response it, because Miss A gave it via verbal stimuli and then he got reinforce and received gesture stimuli, after that he he knew what Miss A meant and gave production. Conversation 2 Miss A (S): (Miss A was drawing something starts with ‘T’ on the whiteboard) Mention something starts with ‘T’! ‘teh’|t?h|,’teh’|t?h|,’teh’|t?h|” T (RS): “Fish! Fish Fiiish! Fish!” (T was answering it louder and louder because his friends were answering too) Miss A (RF): “No, no, no, that is ‘feh’|f?h|,’feh’|t?h|, T, oh look, what is this?” T (P): “Train!” Miss A (RF): “Yes, does it start with ‘T’?” T (P): Yes! Conversation 2 showed how stimuli delivered to T but not only in verbal but also helped by showing picture. Moreover during this conversation, behaviorist learning method happened, because she delivered the material by drilling it, she wanted her students to imitate or think about the answer by knowing the stimuli. Conversation 3 Miss A (S): (Miss A wrote big ‘CAN’ on the whiteboard) “How about this?” Class (RS): “ ‘Ceh’|c?h| ‘ah’ |ah| ‘en’ |?n|” (Some students were answering it loudly but unfortunately T did not give his response and still busy with what he was doing on his table and chair, then Miss B as the teacher assistant came to him) Miss B (RF): “T!, what are you doing? ‘ceh’ |c?h| ’ah’ |ah| ‘en’ |?n|,’ceh’ |c?h|’ah’ |ah| ‘en’|?n|, ‘ceh’|c?h| ‘ah’|ah| ‘en’|?n|, ‘ceh’|c?h| ‘ceh’|c?h| ‘ceh’|c?h| ‘ah’ |ah| ‘en’ |?n| (But T still did not give response and only looked into Miss B), T, ‘ceh’ |c?h| ‘ah’ |ah| ‘en’ |?n|, spell it then write it, come on repeat, ‘ceh’ |c?h| ‘ah’ |ah| ‘en’ |?n|, ‘ceh’ |c?h| ‘ceh’ |c?h|’ceh’ |c?h| ‘ah’ |ah| ‘ah’ |ah|’en’ |?n|” T (P): “ ‘ceh’|c?h| ‘ah’|ah| ‘en’|?n|” (Then wrote it in his paperwork) Conversation 3 is presenting about face to face reinforce and then the process of giving the reinforce is more personal than previous conversations. In this conversation, it can be viewed that longer drilling are being used by the stimuli-giver to the learner. Conversation 4 Miss A (S): (back to English after Mandarin Class, Miss A wrote ‘Tom talks to Ted’ on the whiteboard) “Listen, Tom…talks…to Ted, repeat!” T & Friends (RS): “Tom talks to Ted” (All together) Miss A (RF): “Alright now write letter ‘T’ on the paper and also ‘Tom talks to Ted’” T (P): (T did it well but he more concentrated and interested in something written or doing some drawings and colorings, T wrote his ‘Tom talks to Ted’ perfectly) Conversation 4 shows T is easily absorbing the written stimuli, he got verbal and also written stimuli and then it is showed that he prefers to do writing than speaking. Conversation 5 Miss A (S): “How many rabbits here?” (Asking while pointing to ‘the rabbit’ picture) T (RS): “Five!” (Answering loudly) Miss A (RF): “Four or five?” T (P): “Five!” (Answering while little bit screaming) Conversation 5 is explaining about the evidence of visual learner, he will absorb faster via pictures and sketches and then it can be as good stimulus for the learning activities. When T got stimuli via colorful pictures, he could respond it faster and very interested on it. Conversation 6 Miss A (S): “What is this, Vis? Are you drawing something?” T (RS): “House” (Simple and fast answer) Miss A (RF): “A house?” T (P): “A Zombie house” Conversation 6 is talking about how T as visual learner linked his imagination then drawn it on his paper. Then, T got personality test in the third day of research and during the test T only pointed on the picture also gave his responses and comments about the picture, the results will be ordered based on the test number: T chose ‘Active Kid means he is an extrovert kid and has personality between choleric and sanguine. There are two pictures in for this number, ‘Active Kid’ and ‘Silence Kid’ T chose ‘Crocodile’ picture, question number two represents about color of personality and this picture is symbolizing phlegmatic (green) and melancholic (blue). It looks like this is his minor personality compared to his daily activities. T pointed ‘Menggambar (Drawing)’ picture, this question actually draws activity and hobby. T chose ‘Pemimpin (Leader)’ and this picture symbolized as ‘Red Ranger’. According to this picture, T has tendency for becoming a leader and only choleric, phlegmatic and sanguine have a sense of leadership. T decided to point ‘Happy and Noisy Class’, means that he is dominated by extrovert, it can be choleric or sanguine. DISCUSSION In this part, there will be two sub parts, discussing about behaviorist learning and language development of young learner with visual learning style then another one is talking about personality and learning style. 1. Behaviorist Learning and Language Development of Visual Learner Based on the results above, T is showing that he learned language by drilling and imitating, this is the evidence of behaviorist learning method. According to Brown, language learning is acquisition or ‘getting’, learning is retention of information from the environment around the child (T) or skill, learning is a change in behavior (Brown 2007), based on the result, T tried to acquire language by imitating, undertaking the events, and then writing. Moreover, T also influenced by the environment and also his behavior, environment means he was in rich-knowledge area, in that class the teachers were delivering the materials in English, it would help him to enrich his knowledge in English. More than it, T accompanied by Miss B in order to drilled him until he got an appropriate production. Behavior means he could be controlled by the teachers although he did not focus on the learning because he was visual learner. Behaviorist learning theory totally worked on T, because T was Indonesian and his first language is Bahasa Indonesia but the result was he could speak English and able to acquired the language in very early age. It was helped by stimuli from the teachers, and then they did not give up in giving reinforces until get an appropriate productions. In this case, behaviorist learning method looked fine for visual learner but it needed learning tools, such as pictures or making sketches. Various stimulus were delivered to T and other students such as Verbal stimuli, gesture stimuli, and picture stimuli. Those stimuli reached different range of success, the most successful stimuli is picture stimuli, then followed by gesture stimuli and the last is verbal stimuli. The reason of why the researcher placed the picture stimuli as the most successful stimuli is during the lesson, T got a lot of paperwork and supported by pictures, T looked easier to respond and answer the questions on the paperwork, then when Miss A gave him stimuli via picture such as in the Conversation 2, T could answer it correctly while at first chance he got wrong. Then when Miss A tried to ask about the number of rabbits in the paper, T could do it correctly because the rabbits were drawn there, moreover when Miss A asked him to count it and gave him reinforce he could keep his answer about the amount of the rabbits. It matches with the theory of visual learner, children could focus on something illustrated, it can be symbols or pictures (Monks 1982). Moreover, according to Slavin, children with visual learning style could link words to pictures, and then they could make or create story from their vision and illustrate it into images (Slavin 1986). it happens to T, when Miss A gave materials but T made picture, a zombie house on Conversation 6, then during math session in connecting and counting the carrots and rabbits T did it well. Gesture stimuli stands on the second place, it worked when the verbal stimuli did not work on the students especially T, gesture was working but it was not successful enough like picture stimuli, because gesture stimuli only appeared in a very easy shape such as on the conversation 1, when Miss A gave them stimuli but T and friends did not understand, Miss A acted something big by made something ‘big’ by her hands. It is matching with the writing of Suyadi, one of visual learner characteristics is, prefer watching movies than listening something (Suyadi 2010), watching something same with watching gesture, gesture without sound, it was visible and visual learner could adapt, absorb and understand. Then, verbal stimuli becomes the latest, because visual learner has a weakness, it is difficult for him/her to absorb something verbally, and it happens to T, please look into conversation 3, when Miss A explained about something and T did not focus on her explanation, he just playing with his chair and table, this is proving that T as visual learner was not much interested in verbal instruction or verbal stimuli, again, when Miss B drilled T she must drilled it more than once, it happened because T did not give his response. According to the results above, behaviorist learning method and language development especially for young learner with visual learning style actually connected each other, because T had to get appropriate stimulus and also reinforces in order to acquire language, then behaviorist learning method is becoming one of best way to teach young learner in learning new language, because T is 4 (four) years old student, he still in the period of pre-conceptual thought, and children during this stage are centralized, they will only focus in one dimension and ignore the other dimensions (Monks 1982). Via behaviorist learning method, children will be forced to focus on the stimuli and getting reinforce, indirectly it will develop the vocabulary and can help them to gain appropriate language products. Language not only verbal but also written and T got his own development when he asked to write ‘Tom talks to Ted’ on conversation 4. 2. Personality and Learning Style Personality is a personal characteristic that make consistency in feeling, thinking and also in behavior (Pervin 2010), the test is one of tool in order to know him deeper and trying to reveal the relationship between personality and learning style. There are two pictures for question number one, picture a is ‘active kid’ and then picture b is ‘silence kid’, those pictures are symbolizing four personalities in the human life, ‘active kid’ symbolizes two ‘strong’ personalities, choleric and sanguine, known as personality for an active person, energetic, extrovert and also optimist. Then, picture b, ‘silence kid’ draws two ‘weak; personalities, phlegmatic and melancholic, the characteristics are introvert, the watcher, pessimist, peaceful and also well organized. These two pictures actually bundling the two main roots of personality, extrovert and introvert but only covering the inner self of the subject, based on the result, T already chose picture a ‘active kid’, it means that he is an extrovert person, it is evidenced by T is an active student in the K1 Class, it can be viewed based on conversation 2. Introvert person will think twice to scream and speak loudly, they will not to do that. Question number two has three different pictures with different main colors and focus to know about the personality types, those pictures are symbolizing four personalities, picture a is a dragon with red and yellow as the basic color, but the red almost covers whole the dragon’s body, the red symbolizes choleric, according to Florence Littauer in his book, Personality Plus, choleric person tends to choose strong color to show his power, choleric likes red or another strong color, but most of them choose red (Littauer 1992), picture b is crocodile with ‘snappy birthday’ in it, it has green, blue, yellow, white, red and also white, yet blue and green dominate the picture. Green is color for phlegmatic person, green symbolizes calm, patience, polite, good listener and relax, then blue symbolizes melancholic person, pessimist, good planner, serious, creative, likes list, graphs, diagrams, pictures and then well organized. Then picture c, rainbow and love shaped balloons, very colorful and it impresses like crash in mixing the color, this picture symbolizes sanguine person, sanguine is energetic, funny, talk active, enthusiastic, curious, creative and colorful. Based on the result of personality test, T chose picture b, it is answering that T has introvert part inside, it is normal, according to Eysenck, personality is the more less or stable (Eysenck 1953), it means personality is adapting to the situation, moreover each person has two personalities, major and minor personality, and it balances each other, so T has phlegmatic or melancholic beside his extrovert as the major. Question number three talks about hobby and he chose picture c ‘drawing’, it means that it is correlated with his learning style. Question number four is talking about another side of T, it is not surprising when he chose ‘Red Ranger’ because from the previous question (No. 1) he is an extrovert child and it is getting stronger through his answer. There are three personality types which have tendency to be as leader, the stronger is choleric, followed by phlegmatic and the last is sanguine. Question number five is related to the environment, T chose ‘Happy and Noisy Class’ it is matched with his truly personality, moreover one of visual learner characteristics is able to adapt with noisy situation (Suyadi 2010). Then relating to the test results, T has two different personality, his major is sanguine and hi minor is melancholic. His major, it can be viewed from his daily activities and his relationship towards his friends and the teachers. His minor is melancholic, it is shown from question number two. Then, melancholic person loves to draw something and interest in pictures, graphs or sketches. Relationship between personality and learning style is appeared when he got the task and then he could melt and adapt to the environment. From his major personality, sanguine, he has leadership, sense of coloring, funny, cheerful and then loved by the others, if it is connected with visual learning style, it is related because visual characteristics are good in coloring and also easy to adapt in noisy situation. Then, about his minor melancholic, he is sensitive, interested in pictures, sketches, gestures and imaginative. If it is connected to visual learning style, it is boldly same that visual learner loves to visual stimuli and also creative. It is perfectly match that learning style and personality is related each other because what is in learning style is also occurred in the personality, depends on the environment that may influence it. CONCLUSION Based on the results of the study, there are some facts revealed and can be concluded that the young learner with visual learning style has specific way to acquire language, that is via drilling and imitating, imitating itself is copying the words from the stimuli and also reinforces that delivered by the adults. Then, another way of the young learner in acquiring language is helped by pictures and also gestures when the adults gave the stimuli or reinforces in order to make him reaches appropriate productions, it is suited with his style as visual learner. This study reveals the relationship between personality and learning style, also finds two personalities in the young learner. Between personality and learning style, both of them are connected each other, because as long as T learns through his learning style, the personality will come and influence his style. Because what is in learning style also filled in his personality, but environment will give the massive effect because he has blended personality. Then inside of the young learner, there are major and minor personality, sanguine as major because he is cheerful, colorful, charming, funny and draw crowds, melancholic as minor because he is imaginative, creative, sensitive and also interested in pictures, sketches, and colors. Simpulan menyajikan ringkasan dari uraian mengenai hasil dan pembahasan, mengacu pada tujuan penelitian. Berdasarkan kedua hal tersebut dikembangkan pokok-pokok pikiran baru yang merupakan esensi dari temuan penelitian. SUGGESTION Based on the results of the study, the route of language development in order to reach appropriate product of language will be different each other, although this study only takes one subject but it brings to light that child with different learning style needs different treatment moreover completed by personality. It will be better if in the next research, compare between two different learning styles or more. REFERENCES Brown, H. D. (2007). Principles of Language Learning and Teaching. New York: Pearson Education, Inc. Cecco, J. P. D. (1967). The Psychology of Language, Thought, and Instruction. New York: Holt, Rinehart, and Winston, Inc. DeKeyser, R. M. (2007). Practice in a Second Language: Practice from Applied Linguistics and Cognitive Psychology, New York: Cambridge University Press. Dornyei, Z. (2005). The Psychology of The Language Learner. Mahwah, New Jersey: Lawrence Elbaum Ellis, R. (1985). Understanding Second Language Acquisition. Oxford: Oxford University Press. Linse, C. T. (2005). Practical English Language Teaching: Young Learners. New York: McGraw-Hill Companies, Inc. Littauer, F. (1992). Personality Plus. Michigan: Flemming H. Revell. Monks, F. J. (1982). Psikologi Perkembangan: Pengantar dalam Berbagai Bagiannya. Yogyakarta: Gadjah Mada University Press. Pervin, L. A. (2010). Psikologi Kepribadian. Jakarta: Kencana Predana Media Group. Skehan, P. (1998). A Cognitive Approach to Language Learning. Oxford: Oxford University Press Slavin, R. E. (1986). Educational Psychology. Needham Heights: A Pearson Education Company. Suyadi (2010). Psikologi Belajar Pendidikan Anak Usia Dini. Yogyakarta: Pedagogia. Sutopo, H. B. (1990). Metodologi Penelitian Kualitatif. Surakarta: Universitas Sebelas Maret.